PRIMARY AND SECONDARY PARTS OF SENTENCE IN ENGLISH AND UZBEK LANGUAGES - Gulzinet Berdimuratova Sarsenbekovna; Bafoyeva Nilufar Salimovna (PEDAGOGS, 2024)
Annotation: This article provides a comparative analysis of the primary and secondary parts of sentences in English and Uzbek languages. It examines similarities and differences in sentence structure, word order, agreement, case marking, verb morphology, vocabulary, idiomatic expressions, formality, and register between the two languages. Through examples and explanations, the article offers insights into how sentences are constructed and how language elements function in each linguistic context. Understanding these differences enhances comprehension and proficiency in both English and Uzbek languages.